Analysis of Factors Affecting Performance Improvement of Health Officers at Abuya Hospital, Sumenep Regency - Yuly Peristiowati; Hidayatur Rahman (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
Performance is the result of work achieved by a person or group in an organization within a certain period of time, in accordance with their respective authorities and responsibilities.The purpose of this study is to analyze the effect of rewards, work facilities and work coaching on improving the performance of health workers at the Abuya Hospital, Sumenep Regency. The design of this research is an observational quantitative research with a cross sectional approach with the focus of the research being directed at analyzingthe effect of rewards, work facilities and work coaching on improving the performance of health workers at the Abuya Hospital, Sumenep Regency. The total population is 287 respondents and a sample of 167 respondents is taken using the Simple Random Sampling technique. In the study, it was found that almost half of the respondents had a good reward category as many as 76 respondents (46%). Almost half of the respondents have good working facilities as many as 77 respondents (46%). Almost half of the respondents have job coaching in the sufficient category as many as 72 respondents (43%). Almost half of the respondents have a good performance as many as 82 respondents (49%). Based on the results of Multiple Linear Regression analysis shows that with a p-value of 0.000 <0.05 then H1 is accepted so it can be concluded that there is a simultaneous effect of reward, work facilities and work development on improving the performance of health workers at the Abuya Hospital, Sumenep Regency with an effect of 74.9%. It is hoped that health workers will be able to provide health services to the community more optimally, namely by improving better performance, so that the goal of improving public health status can be realized properly.